Traditional Tomato Varieties Improve Fruit Quality Without Affecting Fruit Yield Under Moderate Salt Stress - Meza, Silvia L. R.; Egea, Isabel; Massaretto, Isabel L.; Morales, Belén; Purgatto, Eduardo; Egea-Fernández, José M.; Bolarin, María C.; Flores, Francisco B. (Frontiers in Plant Science, 2020)
Identification of tomato varieties able to exhibit higher accumulation of primary and secondary metabolites in their fruits is currently a main objective in tomato breeding. One tool to improve fruit quality is to cultivate the plants under salt stress, although improvement of fruit quality is generally accompanied by productivity losses. However, it is very interesting to implement strategies aiming at enhancing fruit quality of tomato by means of growing plants in moderate salt stress that allows for a sustainable fruit yield. The traditional tomato varieties adapted to the Mediterranean environmental constraints may be very attractive plant materials to achieve this goal, given the wide range of fruit quality traits because of their genetic diversity. Here, agronomic responses and fruit quality traits, including primary and secondary metabolites, were analyzed in fruits of two Mediterranean traditional tomato varieties named “Tomate Pimiento” (“TP”) and “Muchamiel Aperado” (“MA”) because of the pepper and pear shape of their fruits, using as reference the commercial cultivar “Moneymaker” (“MM”). Plants were grown without salt (control) and with moderate salt stress (50 mM NaCl), which did not affect fruit yield in any variety. “TP” is of great interest because of its high soluble solids content (SSC) in control, which is even higher in salt, whereas “MA” is very attractive because of its high Brix yield index (SSC × fruit yield), used as overall fruit quality measure. Similitude between both traditional varieties were found for primary metabolism, as they significantly increased sucrose contents compared with “MM” in red ripe fruits from plants in control and, especially, salt stress conditions. The most remarkable difference was the high constitutive levels of total amino acids in “TP” fruits, including the three major free amino acids found in tomato fruit, GABA, glutamate, and glutamine, which even increased under salinity. Regarding secondary metabolites, the most interesting change induced by salinity was the increase in α-tocopherol found in red ripe fruits of both “TP” and “MA.” These results reveal the interest of traditional varieties as sources of genetic variation in breeding because of their improvement of tomato fruit quality without production losses under moderate salt stress.